Enhancing Student Engagement in IPAS: The Impact of The Picture and Picture Learning Model in Grade I at SD Muhammadiyah 2 Kauman Surakarta - Suranto, S; Monalisa, Lusiani (Proceedings International Conference on Education Innovation and Social Science, 2024)
This research aims to increase students' active learning through the application of the picture and picture learning model in IPAS subjects. The data collection technique in this research uses observations carried out in the classroom. The subjects of this research were all students in class 1B of SD Muhammadiyah 2 Kauman Surakarta, totaling 28 students. The results of the research showed that there was an increase in activeness in the learning process with the acquisition of activeness data during the pre-cycle, namely from 28 students there were 11 students who were active in learning with a percentage of 39%, increasing to 18 students who were active in learning with a percentage of 64% in the cycle I. Then there was an increase in cycle II, namely 23 students who were active in learning with a percentage of 82%. The increase in students' learning activeness occurs because students understand the learning material using the picture and picture learning model and students are more enthusiastic in participating in the learning process.